PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH BERBANTUAN MEDIA WORDWALL TERHADAP HASIL BELAJAR - Gia Aprialda; Ai Nur Solihat; Rendra Gumilar (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2024)
The low learning outcomes of students in economics subjects are one of the learning problems at Singaparna 1 Public High School. This happened because there were still several students in class. This research was conducted to determine the effect of implementing the Make a Match cooperative learning model assisted by Wordwall media on student learning outcomes. This research uses a quasi-experimental method with a non-equivalent control group design. The data analysis technique uses a paired sample t-test and an independent sample t-test. The research results show that 1) there are differences in student learning outcomes in classes that use the Make a Match type cooperative learning model assisted by Wordwall media before and after treatment, with an average N-Gain value of 0.71 (high). 2) There are differences in student learning outcomes in classes that use conventional learning models before and after treatment, with an average N-Gain value of 0.46 (medium). 3) There is a difference in the increase in student learning outcomes in classes that use the Make a Match type of cooperative learning model assisted by Wordwall media and classes that use conventional learning models after treatment.